転子果長測定における大転子測定点に関する調査 - 大谷 拓哉; 雄賀多 聡; 三和 真人 (形態・機能, 2016)
The purpose of this study is to identify the detailed points of the greater trochanter where physical therapists choose as a landmark to measure the trochanter-malleolar distance. The subjects were 33 physical therapists affiliated with 6 medical facilities. The therapists placed markers on the region of the greater trochanter in the femur model where they set measurement points to determine trochanter-malleolar distance. Photos of the markers were taken with a digital camera. The digital photos of the markers were analyzed with ImageJ (National Institute of Health). Most markers were found around the most externally prominent point of the greater trochanter. A few markers were found on the upper, posterior, and inferior-anterior aspect of the greater trochanter. These results suggest that standardized measurement points for the greater trochanter are necessary to improve inter-rater reliability in the measurement of trochanter-malleolar distance. 本研究の目的は、理学療法士が転子果長測定時にランドマークとする大転子のどの部位を測定点としているかを明らかにすることである。対象は6か所の医療施設に勤務する理学療法士33名とした。大腿骨模型を用いて、転子果長測定時に大転子の中で測定点とする部位にマーカーを貼付してもらった。マーカーをデジタルカメラで撮影し、画像解析ソフトを用いてマーカー座標を同定した。分析の結果、多くのマーカーが大転子の最外突出部付近に存在したが、大転子の上端部、下部、後部にもマーカーが存在し、全体として広範囲な分布が認められた。転子果長測定における検者間信頼性向上のためには大転子測定点の統一が必要と考えられる。